2016
DOI: 10.1182/blood-2015-09-669929
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thrombopoietin but not G-CSF receptor stimulation induces self-renewing hematopoietic stem cell divisions in vivo

Abstract: Key Points• Mpl agonist, but not granulocyte colonystimulating factor, induces self-renewing HSC divisions and expansions.In steady-state adult hematopoiesis, most hematopoietic stem cells (HSCs) are in the resting phase of the cell cycle. Upon enhanced hematopoietic demand, HSCs can be induced to divide and self-renew or differentiate. However, the cell-extrinsic signals inducing HSC cycling remain to be elucidated. Using in vivo high-resolution single HSC divisional tracking, we directly demonstrate that cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…The activation of PRR in HSPCs leads to enhanced proliferation, increased mobilization from the BM, reduced self-renewal, and myelopoiesis-favoring differentiation (Figure 1C). Since HSPCs also express a broad spectrum of inflammatory cytokine/chemokine receptors (12, 93), they can detect milieu broad range of pro-inflammatory signals via their respective receptors, released systemically or locally by activated immune cells in response to infectious challenges, e.g., IFN-α/γ (9498) (Figure 3). These two pathways are not mutually exclusive: G-CSF stimulation impairs HSC repopulating potential through upregulation of TLR-2 and -4 expressions and activation of the subsequent signaling in HSCs (99).…”
Section: Inflammation In Hematopoiesismentioning
confidence: 99%
“…The activation of PRR in HSPCs leads to enhanced proliferation, increased mobilization from the BM, reduced self-renewal, and myelopoiesis-favoring differentiation (Figure 1C). Since HSPCs also express a broad spectrum of inflammatory cytokine/chemokine receptors (12, 93), they can detect milieu broad range of pro-inflammatory signals via their respective receptors, released systemically or locally by activated immune cells in response to infectious challenges, e.g., IFN-α/γ (9498) (Figure 3). These two pathways are not mutually exclusive: G-CSF stimulation impairs HSC repopulating potential through upregulation of TLR-2 and -4 expressions and activation of the subsequent signaling in HSCs (99).…”
Section: Inflammation In Hematopoiesismentioning
confidence: 99%
“…We previously highlighted that mouse HSCs express integrin avb3 (CD51/CD61) higher than progenitor cells (Umemoto et al, 2006). Integrin b3 signaling contributes to the maintenance of HSCs by stimulating long-term repopulating (LTR) activity, collaborating with thrombopoietin (TPO) (Umemoto et al, 2012), a crucial cytokine for HSC maintenance, quiescence (Qian et al, 2007;Yoshihara et al, 2007), and proliferation (Kimura et al, 1998;Fox et al, 2002;Kovtonyuk et al, 2016). By contrast, in the presence of interferon-c (IFNc), integrin b3 signaling diminished LTR activity of HSCs even in the presence of TPO (Ishihara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this report, most of the cases involved continuous administration, but one case was discontinued because of side effects, although a long-term increase of neutrophil count was observed. Larisa et al reported a TPO agonist induces self-renewing HSCs in mice [13]. In addition, Kuter et al reported TPO is a physiological factor mediating the feedback loop between circulating platelets and bone marrow MKs [14].…”
Section: Discussionmentioning
confidence: 99%